Adductor Canal Block Provides Noninferior Analgesia and Superior Quadriceps Strength Compared With Femoral Nerve Block in Anterior Cruciate Ligament Reconstruction. Issue 6 (December 2016) - Abdallah, Faraj W.; Whelan, Daniel B.; Chan, Vincent W.; Prasad, Govindarajulu A.; Endersby, Ryan V.; Theodoropolous, John; Oldfield, Stephanie; Oh, Justin; Brull, Richard
Abstract : (Abstracted from Anesthesiology, 124:1053–1064, 2016) Adductor canal block (ACB) for total knee arthroplasty is an alternative to using femoral nerve block (FNB) and offers the advantage of preserving the motor function of the quadriceps femoris muscle. However, the analgesic and motor-sparing benefits of ACB for anterior cruciate ligament (ACL) reconstruction remain unknown, owing to differences in pain generators between knee arthroplasty and ACL reconstruction.